2014
DOI: 10.1177/1082013214538984
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of alternative protein in gluten-free product development

Abstract: Celiac disease is an immune-mediated disease triggered in genetically susceptible individuals by ingested gluten from wheat, rye, barley, and other closely related cereal grains. The current treatment for celiac disease is life-long adherence to a strict gluten-exclusion diet. The replacement of gluten presents a significant technological challenge, as it is an essential structure-building protein, which is necessary for formulating high-quality baked goods. A major limitation in the production of gluten-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 94 publications
(196 reference statements)
0
28
0
Order By: Relevance
“…Details about the proteins from these sources were shown in Table 2. Addition of proteins can not only enhance the functional and nutritional properties of GF products but also improve sensory quality by increasing Maillard browning and flavor (Deora et al, 2015). Ziobro et al (2016) checked the effects of selected protein isolates (albumin, collagen, pea, lupine, and soy) and concentrates on the structure and quality of GFB without the introduction of any other structure forming additives such as guar gum and pectin.…”
Section: Additives In Gluten-free Bread Makingmentioning
confidence: 99%
“…Details about the proteins from these sources were shown in Table 2. Addition of proteins can not only enhance the functional and nutritional properties of GF products but also improve sensory quality by increasing Maillard browning and flavor (Deora et al, 2015). Ziobro et al (2016) checked the effects of selected protein isolates (albumin, collagen, pea, lupine, and soy) and concentrates on the structure and quality of GFB without the introduction of any other structure forming additives such as guar gum and pectin.…”
Section: Additives In Gluten-free Bread Makingmentioning
confidence: 99%
“…Their presence may influence storage of glutenfree products, and decrease bread staling. Protein could be added in various forms, as components of gluten-free flours (e.g., rice, soy, pea) or in the form of concentrates and isolates (Deora et al 2015). The formation of dough and bread structure by protein addition is often assisted by the introduction of other supplements such as polysaccharide hydrocolloids, enzymes or surfactants.…”
Section: Research Highlightsmentioning
confidence: 99%
“…The formation of dough and bread structure by protein addition is often assisted by the introduction of other supplements such as polysaccharide hydrocolloids, enzymes or surfactants. Among cereal proteins zein and kaffirin have been applied for gluten-free bread supplementation (Deora et al 2015;Pontieri et al 2013;Schober et al 2011). Andersson et al (2011) observed that the addition of corn protein in the presence of hydrocolloids positively influences dough rheology, improves bread structure and increase its volume.…”
Section: Research Highlightsmentioning
confidence: 99%
See 2 more Smart Citations